2015
DOI: 10.1007/s10765-015-1842-2
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Enthalpy/Entropy Variation and Structure of Cu–Al–Mn–Fe Shape Memory Alloys

Abstract: Cu-based Cu-Al-Mn-Fe shape memory alloys were produced in an arc melter under vacuum. The crystal structure of the fabricated alloys were determined by means of X-ray diffraction (XRD). The XRD analysis results indicated that the martensitic phase of the samples have an M18R structure. The characteristic transformation temperatures, thermodynamic parameters, and the activation energy values of the samples according to Kissinger and Ozawa methods were determined by differential scanning calorimetry measurements… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…He reported that addition of Fe, Au, Zn, Ni and Ti improves shape memory effect (SM) of alloys, while Co, Si, Sn and Cr decrease temperature of martensitic transformation (M s ) as well as their ability to coldworkability. The effect of Ce on the microstructure and phase transformation temperatures on Cu-Al-Mn SMA alloy was reported by Chen [11], while Canbay presented the effect of Fe on the enthalpy and entropy values of Cu-Al-Mn-Fe system [12].…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…He reported that addition of Fe, Au, Zn, Ni and Ti improves shape memory effect (SM) of alloys, while Co, Si, Sn and Cr decrease temperature of martensitic transformation (M s ) as well as their ability to coldworkability. The effect of Ce on the microstructure and phase transformation temperatures on Cu-Al-Mn SMA alloy was reported by Chen [11], while Canbay presented the effect of Fe on the enthalpy and entropy values of Cu-Al-Mn-Fe system [12].…”
Section: Introductionmentioning
confidence: 83%
“…Cu-Al-Mn alloys display advantage in technological applications over other Cu-based SMA alloys, such as Cu-Al-Ni, Cu-Al-Zn etc., according to significantly higher ductility and ability of cold deformation [5,6]. The addition of quaternary element to Cu-Al-Mn alloys, improves their properties and meet the standards for application as sensors or actuators, in automotive industry, robotics, aerospace or biomedical sectors [7][8][9]. Sutou and co-authors investigated the influence of Ti, Cr, Co, Fe, Ag, Au, Ni, Zn, Si and Sn on the shape memory effect and pseudoelasticity of Cu-Al-Mn alloys [10].…”
Section: Introductionmentioning
confidence: 99%
“…The maximum SME value obtained was 4.4% for Nb and Zr contents of 1% and 2%, respectively. More recent studies related to the Cu-Al-Fe-Mn system can be found in the literature [105][106][107].…”
Section: Invited Feature Paper-reviewmentioning
confidence: 99%
“…SMAs such as Cu-based binary and ternary systems (Cu-Zn, Cu-Al, Cu-Zn-Al, Cu-Al-Ni, Cu-Al-Mn), Ni-Ti, and high-temperature shape memory alloys (HTSMA) are usually used in the automotive, aerospace, and medical fields (Baiz, Canbay, & Ozkul, 2018). Furthermore, intelligent materials attract attention in today's technological advances (Canbay, Gudeloglu, & Genc, 2015).…”
Section: Introductionmentioning
confidence: 99%